Asas Kepastian Hukum Dalam Perpajakan Di Indonesia - Bonaraja Purba; Hasyim Hasyim; Ine Febrianti Siregar; Rifka Fauziah Batubara; Ruth Septaria Hutapea; Sinta Rahmawati (JURNAL RISET MANAJEMEN (JURMA), 2023)
Law is a rule for humans, so the implementation of the law must be carried out to provide benefits, usefulness for the community in society. People who get good and right treatment will create a peaceful state of affairs. The law can protect the rights and obligations of each individual which are solid and manifest in general. There are three objectives of law, namely justice, benefit and legal certainty. Justice is the main thing of the three things, but it does not mean that the other two elements can be simply ignored. Good law is law that is able to synergize these three elements for the welfare and prosperity of society. The research method used by the author is Normative Juridical, with data collection tools through library research. The results of the research show that legal certainty is a guarantee that the law is enforced, that those entitled according to law can obtain their rights and that decisions can be implemented. Legal certainty is a justifiable protection against arbitrary actions which means that someone will be able to get something that is expected in certain circumstances.